Nexus of consumer trust in FinTok influencers, consumer engagement, data privacy concern, financial literacy and travel scam avoidance - Umer Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2025)
This study aims to investigate the effectiveness of FinTok influencers in preventing online travel scams by enhancing consumer trust, financial literacy, and data privacy concerns. The research examines how these influencers can contribute to improving consumer protection and safety in digital transactions. A survey was conducted with a sample of 250 TikTok users (who actively follow FinTok influencers) and have booked travel online at least once. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS software, the study analyzed the relationships between consumer trust, financial literacy, and data privacy concerns in mitigating exposure to travel scam. PLS-SEM estimations indicate that FinTok influencers play a significant role in building consumer trust and enhancing financial literacy and data privacy concerns, which, in turn, reduce susceptibility to online travel scams. Consumer engagement emerged as a critical mediator, emphasizing the need for influencers to maintain credibility and transparency. Additionally, financial literacy was identified as a key factor in empowering consumers to make informed decisions and avoid travel scams. This study contributes to the literature on digital consumer protection by highlighting the potential of social media influencers in combating online fraud. By focusing on the niche of FinTok, it provides practical insights for organizations seeking to leverage influencers for promoting financial literacy and consumer safety.
Keywords: 330; FinTok influencers; consumer trust; data privacy concern; financial literacy; consumer engagement; travel scam avoidance; Finfluencers; financial influencers